Math, asked by krishtinasingh010207, 8 months ago

c. Answer the following questions in about 30 words each.
1. How did the woman know the narrator? Why did she want to meet him?
2. What impression did the narrator gather of the woman when he met her?
4. Why did the narrator order coffee for himself also?
walter carry a basket full of
2. Why was the narrator pante-stricken while they were waiting for the asparagus
to be cooked?
3. What is the waiter's contribution in allowing the woman to have a gorgeous meal?​

Answers

Answered by Amrit111Raj82
9

Question:

Solve the given equation:

\displaystyle{\sf\:\dfrac{\dfrac{x}{3}\:-\:\dfrac{2}{5}}{\dfrac{3}{4}\:-\:2x}\:=\:\dfrac{16}{15}}

4

3

−2x

3

x

5

2

=

15

16

Answer:

The value of x is

\displaystyle{\implies\boxed{\red{\sf\:x\:=\:\dfrac{18}{37}}}}⟹

x=

37

18

Step-by-step-explanation:

The given equation is \displaystyle\sf\:\dfrac{\dfrac{x}{3}\:-\:\dfrac{2}{5}}{\dfrac{3}{4}\:-\:2x}\:=\:\dfrac{16}{15}

4

3

−2x

3

x

5

2

=

15

16

.

Now,

\displaystyle{\sf\:\dfrac{\dfrac{x}{3}\:-\:\dfrac{2}{5}}{\dfrac{3}{4}\:-\:2x}\:=\:\dfrac{16}{15}}

4

3

−2x

3

x

5

2

=

15

16

\displaystyle{\implies\sf\:\dfrac{\dfrac{5x\:-\:6}{15}}{\dfrac{3\:-\:8x}{4}}\:=\:\dfrac{16}{15}}⟹

4

3−8x

15

5x−6

=

15

16

\displaystyle{\implies\sf\:\dfrac{5x\:-\:6}{15}\:\times\:\dfrac{4}{3\:-\:8x}\:=\:\dfrac{16}{15}}⟹

15

5x−6

×

3−8x

4

=

15

16

\displaystyle{\implies\sf\:\dfrac{4\:\times\:(\:5x\:-\:6\:)}{15\:\times\:(\:3\:-\:8x\:)}\:=\:\dfrac{16}{15}}⟹

15×(3−8x)

4×(5x−6)

=

15

16

\displaystyle{\implies\sf\:\dfrac{20x\:-\:24}{45\:-\:120x}\:=\:\dfrac{16}{15}}⟹

45−120x

20x−24

=

15

16

\displaystyle{\implies\sf\:15\:\times\:(\:20x\:-\:24\:)\:=\:16\:\times\:(\:45\:-\:120x\:)}⟹15×(20x−24)=16×(45−120x)

\displaystyle{\implies\sf\:300x\:-\:360\:=\:720\:-\:1920x}⟹300x−360=720−1920x

\displaystyle{\implies\sf\:300x\:+\:1920x\:=\:720\:+\:360}⟹300x+1920x=720+360

\displaystyle{\implies\sf\:2220x\:=\:1080}⟹2220x=1080

\displaystyle{\implies\sf\:x\:=\:{\dfrac{108\cancel{0}}{222\cancel{0}}}}⟹x=

222

0

108

0

\displaystyle{\implies\sf\:x\:=\:\cancel{\dfrac{108}{222}}}⟹x=

222

108

\displaystyle{\implies\boxed{\red{\sf\:x\:=\:\dfrac{18}{37}}}}⟹

x=

37

18

─────────────────────

Verification:

The given equation is

\displaystyle{\sf\:\dfrac{\dfrac{x}{3}\:-\:\dfrac{2}{5}}{\dfrac{3}{4}\:-\:2x}\:=\:\dfrac{16}{15}}

4

3

−2x

3

x

5

2

=

15

16

The value of x is \displaystyle\sf\:\dfrac{18}{37}

37

18

By substituting this value of x in the LHS of the given equation, we get,

\displaystyle\sf\:LHS\:=\:\dfrac{\dfrac{x}{3}\:-\:\dfrac{2}{5}}{\dfrac{3}{4}\:-\:2x}LHS=

4

3

−2x

3

x

5

2

\displaystyle{\implies\sf\:LHS\:=\:\dfrac{\dfrac{\dfrac{18}{37}}{3}\:-\:\dfrac{2}{5}}{\dfrac{3}{4}\:-\:2\:\times\:\dfrac{18}{37}}}⟹LHS=

4

3

−2×

37

18

3

37

18

5

2

\displaystyle{\implies\sf\:LHS\:=\:\dfrac{\dfrac{\cancel{18}}{37}\:\times\:\dfrac{1}{\cancel{3}}\:-\:\dfrac{2}{5}}{\dfrac{3}{4}\:-\:\dfrac{39}{37}}}⟹LHS=

4

3

37

39

37

18

×

3

1

5

2

\displaystyle{\implies\sf\:LHS\:=\:\dfrac{\dfrac{6}{37}\:-\:\dfrac{2}{5}}{\dfrac{3}{4}\:-\:\dfrac{36}{37}}}⟹LHS=

4

3

37

36

37

6

5

2

\displaystyle{\implies\sf\:LHS\:=\:\dfrac{\dfrac{6\:\times\:5\:-\:2\:\times\:37}{37\:\times\:5}}{\dfrac{3\:\times\:37\:-\:36\:\times\:4}{4\:\times\:37}}}⟹LHS=

4×37

3×37−36×4

37×5

6×5−2×37

\displaystyle{\implies\sf\:LHS\:=\:\dfrac{\dfrac{30\:-\:74}{185}}{\dfrac{111\:-\:144}{148}}}⟹LHS=

148

111−144

185

30−74

\displaystyle{\implies\sf\:LHS\:=\:\dfrac{\dfrac{-\:44}{185}}{\dfrac{-\:33}{148}}}⟹LHS=

148

−33

185

−44

\displaystyle{\implies\sf\:LHS\:=\:\dfrac{\cancel{-}\:44}{185}\:\times\:\dfrac{148}{\cancel{-}\:33}}⟹LHS=

185

44

×

33

148

\displaystyle{\implies\sf\:LHS\:=\:\cancel{\dfrac{\cancel{44}}{185}}\:\times\:\dfrac{148}{\cancel{33}}}⟹LHS=

185

44

×

33

148

\displaystyle{\implies\sf\:LHS\:=\:\dfrac{4}{185}\:\times\:\dfrac{148}{3}}⟹LHS=

185

4

×

3

148

\displaystyle{\implies\sf\:LHS\:=\:\dfrac{4\:\times\:148}{185\:\times\:3}}⟹LHS=

185×3

4×148

\displaystyle{\implies\sf\:LHS\:=\:\cancel{\dfrac{592}{555}}}⟹LHS=

555

592

\displaystyle{\implies\sf\:LHS\:=\:\dfrac{16}{15}}⟹LHS=

15

16

\displaystyle{\implies\sf\:RHS\:=\:\dfrac{16}{15}}⟹RHS=

15

16

\displaystyle{\implies\boxed{\red{\sf\:LHS\:=\:RHS}}}⟹

LHS=RHS

Hence verified!

Answered by Amrita555Rani
11

 \huge \mathfrak { \color{blue}{ \underline{ \underline{Answer}}} }

 \sf{ \color{red}{a) \: 2 \times 3 + 9 - 3 \times 3 \times ( - 3)}}

 \sf{ \color{red}{6 + 9   - ( -  27)}}

 \sf { \red{6 + 9 + 27}}

 \sf{ \red{15 + 27}}

 { \bold{ \red{42}}}

Similar questions